Ungulate Detection and Species Classification from Camera Trap Images Using RetinaNet and Faster R-CNN - Vecvanags, Alekss; Aktas, Kadir; Pavlovs, Ilja; Avots, Egils; Filipovs, Jevgenijs; Brauns, Agris; Done, Gundega; Jakovels, Dainis; Anbarjafari, Gholamreza (MDPI)
Changes in the ungulate population density in the wild has impacts on both the wildlife and human society. In order to control the ungulate population movement, monitoring systems such as camera trap networks have been implemented in a non-invasive setup. However, such systems produce a large number of images as the output, hence making it very resource consuming to manually detect the animals. In this paper, we present a new dataset of wild ungulates which was collected in Latvia. Moreover, we demonstrate two methods, which use RetinaNet and Faster R-CNN as backbones, respectively, to detect the animals in the images. We discuss the optimization of training and impact of data augmentation on the performance. Finally, we show the result of aforementioned tune networks over the real world data collected in Latvia.
Keywords: ungulates; camera traps; animal detection; Faster R-CNN; RetinaNet